The Moderating Role Of Sustainability Disclosure: Tax Avoidance And Firm Value - Ardian Azmi Hasibuan; Amrie Firmansyah (WIM Solusi Prima, 2023)
A company's performance is very important because it will impact the decision-making of shareholders and investors. As reflected in increased share prices, companies with good performance tend to increase company value. One factor that can influence company value is tax avoidance. This research examines the effect of avoidance on company value with sustainability report disclosure as a moderating variable. This research uses quantitative data from financial and sustainability reports of banking sub-sector companies from 2020 to 2022. Data was obtained from the websites of each company. Using purposive sampling, 41 samples were obtained and tested using multiple regression analysis for cross-section data. This research concludes that tax avoidance has a negative effect on company value. Meanwhile, sustainability disclosures do not mediate. This research contributes to providing capital market-based financial accounting research literature from the perspective of company policy as reflected in the financial information of banking companies in Indonesia.